A biodegradable butene glycol-based polyester elastomer tread rubber and preparation method thereof
By using butene glycol-based polyester elastomer to prepare tread glue materials, the problems of non-biodegradable and insufficient mechanical properties of existing tread glue materials are solved, and high mechanical properties and biodegradable tread glue materials are achieved to meet the actual needs of tires and reduce environmental pollution.
Patent Information
- Application Number
- CN202210201488.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-03-18
- Filing Date
- 2022-03-02
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2042-03-02
AI Technical Summary
The existing tread glue materials are not biodegradable, resulting in environmental pollution and health risks, and their mechanical properties are not enough to meet the actual needs of tires.
Butylene glycol-based polyester elastomer is used as the raw material of the new tread glue material, and tread glue materials with high mechanical properties and biodegradable are prepared through esterification and polymerization.
The high mechanical properties and biodegradability of the tread glue material are achieved, which can meet the actual use needs of tires, and can be biodegradable after use, reducing environmental pollution.
Smart Images

Figure CN115109400B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of rubber, and more particularly to a biodegradable butene glycol-based polyester elastomer tread rubber and a preparation method thereof. Background Art
[0002] Due to its unique high elasticity, rubber materials are widely used in various fields of national defense and people's livelihood, and are an important strategic resource for a country. Tires are the most widely used field for rubber materials. However, while tires provide convenience for human production and life, they also cause a series of hidden dangers to the environment and human health. First, the large amount of discarded and accumulated waste tires every year will not only seriously pollute the environment, but also cause fire hazards. Second, the wear and tear microparticles produced by the wear of tires, especially the tread rubber part during use, also have a very serious impact on the atmosphere and human health. Therefore, it is of great significance to develop biodegradable tire tread rubber materials.
[0003] In fact, currently available commercial tread rubber materials are not biodegradable because the main chains of commercially available traditional rubbers, such as natural rubber, styrene-butadiene rubber, butadiene rubber, etc., do not contain biodegradable groups. However, polyester elastomers, which have emerged in recent years, have the potential to prepare biodegradable tread rubber materials because their main chains contain a large number of biodegradable ester groups.
[0004] Patent CN101450985A "A polyester-type bioengineering rubber and its preparation method" discloses a method for preparing a polyester elastomer / white carbon black (or carbon black) nanocomposite material with degradation potential based on a synthetic polyester elastomer. However, the double bond donor in the polyester elastomer used is itaconic acid containing highly active conjugated double bonds, which belongs to an itaconic acid-based polyester elastomer with a low number average molecular weight; and when it is vulcanized, the amount of peroxide crosslinking agent used is low, so the crosslinking controllability of the composite material is poor. In addition, the tensile strength of the obtained composite material is generally lower than 16MPa, and the 300% elongation stress is also low, which makes it difficult to meet the actual application requirements of tire tread rubber materials.
[0005] Therefore, it is necessary to develop a tire tread rubber prepared from a new type of polyester elastomer. Compared with itaconic acid-based polyester elastomers with the same double bond content, the new polyester elastomer needs to have the characteristics of high number average molecular weight and narrow molecular weight distribution, and the amount of peroxide crosslinking agent consumed during crosslinking is equivalent to that of traditional rubber materials, and the crosslinking controllability is better, so as to prepare a biodegradable polyester elastomer tread rubber material with high mechanical properties. Summary of the invention
[0006] In order to solve the technical problems existing in the prior art, the present invention provides a biodegradable butene glycol-based polyester elastomer tread rubber and a preparation method thereof.
[0007] The present invention uses biodegradable butene glycol-based polyester elastomer as raw rubber material. The butene glycol-based polyester elastomer is a new polyester elastomer using butene glycol with highly stable non-conjugated double bonds as a double bond donor. Compared with itaconic acid-based polyester elastomers with the same double bond content, the butene glycol-based polyester elastomer has the characteristics of high number average molecular weight and narrow molecular weight distribution. The amount of peroxide crosslinking agent consumed during crosslinking is equivalent to that of traditional rubber materials, and the crosslinking controllability is better.
[0008] Therefore, the present invention develops a biodegradable butene glycol-based polyester elastomer tread rubber material having high mechanical properties based on the butene glycol-based polyester elastomer.
[0009] One of the objects of the present invention is to provide a biodegradable butene glycol-based polyester elastomer tread rubber.
[0010] The tread rubber is made of components including a butene glycol-based polyester elastomer, a nano filler, a peroxide cross-linking agent, and other compounding aids;
[0011] Taking the butene glycol-based polyester elastomer as 100 parts by weight, the components are calculated by weight:
[0012]
[0013] In a preferred embodiment of the present invention,
[0014] The butene glycol-based polyester elastomer is a butene glycol-based aliphatic polyester elastomer or a butene glycol-based aliphatic-aromatic copolyester elastomer.
[0015] In a preferred embodiment of the present invention,
[0016] The butene glycol-based aliphatic polyester elastomer of the present invention is a polyester elastomer in a patent application (application number 202010045414.1, invention name “A butene glycol-based polyester elastomer and preparation method”), which is cited in its entirety herein.
[0017] The structure of the butene glycol-based aliphatic polyester elastomer is shown below:
[0018]
[0019] R m1 , R m2 is a branched or unbranched chain alkyl group, R m1 , R m2 can be the same or different; wherein m1, m2 represent the number of carbon atoms, 2≤m1≤14; preferably 2≤m1≤10; 2≤m2≤14; preferably 2≤m2≤10; m1, m2 can be equal or unequal;
[0020] R n1 , R n2 is a branched or unbranched chain alkyl group, R n1 , R n2 Can be the same or different; wherein n1, n2 represent the number of carbon atoms, 2≤n1≤12, preferably 2≤n1≤8; 2≤n2≤12; preferably 2≤n2≤8;; n1, n2 can be equal or different;
[0021] x and y are integers from 1 to 3, and x and y may be equal or different.
[0022] a, b, c, d, e, f, g, h, i, j, k, l, m, n, and o represent the degree of polymerization;
[0023] Among them, a, c, m, o are not 0 at the same time; e and k are not 0 at the same time; the others can be 0 at the same time;
[0024] The preparation method comprises:
[0025] The diol, dibasic acid and / or lactic acid, antioxidant and polymerization inhibitor are subjected to esterification reaction and polymerization reaction under the action of a catalyst to obtain a butene glycol-based polyester elastomer;
[0026] The diols are 1,4-butene diol and other diols; the other diols are HO-R m -OH, diethylene glycol, triethylene glycol, tetraethylene glycol or a combination thereof;
[0027] Among them, R m is a branched or unbranched chain alkyl group, wherein m represents the number of carbon atoms, 2≤m≤14; preferably 2≤m≤10;
[0028] The dibasic acid is HOOC-R n -One or a combination of COOH;
[0029] Among them, R n It is a branched or unbranched chain alkyl group, wherein n represents the number of carbon atoms, 2≤n≤12, preferably 2≤n≤8.
[0030] Among them, preferred:
[0031] The molar percentage of 1,4-butenediol in the diol is 2% to 60%, more preferably 5% to 30%.
[0032] The catalyst can be a conventional catalyst in the prior art, and in the present invention, it can be preferably one or a combination of selenium dioxide, antimony trioxide, ethylene glycol antimony, p-toluenesulfonic acid, acetate, alkyl aluminum with 1 to 12 carbon atoms, organic tin compounds and titanate; in view of the problem of heavy metal residues in polyester products, titanate catalysts without heavy metal elements, such as tetrabutyl titanate, tetraisopropyl titanate, etc., are preferred. It can be added in the esterification section or in the pre-condensation section, and the amount of the catalyst is 0.02 to 0.5% of the total mass of the diol, dibasic acid and / or lactic acid.
[0033] The antioxidant can be a conventional antioxidant in the prior art, and in the present invention, it can be preferably a phosphoric acid or phosphorous acid compound, preferably one or two of phosphoric acid, phosphorous acid, phosphate ester, phosphite ester, phenyl phosphate, and phenyl phosphite. The amount of the antioxidant is 0.01-0.2% of the total mass of the diol, dibasic acid and / or lactic acid; preferably 0.04-0.08%;
[0034] The polymerization inhibitor can be a conventional polymerization inhibitor in the prior art, and in the present invention, it can be preferably a phenolic polymerization inhibitor, an ether polymerization inhibitor, a quinone polymerization inhibitor or an aromatic amine polymerization inhibitor, preferably one or two of hydroquinone, p-tert-butylcatechol, p-hydroxyanisole, benzoquinone, diphenylamine, and p-phenylenediamine. The amount of the polymerization inhibitor is 0.01-0.5% of the total mass of the diol, dibasic acid and / or lactic acid; preferably 0.05-0.2%.
[0035] The molar ratio of the alcohol to the acid of the diol, the dibasic acid and / or the lactic acid is 1.05:1 to 1.8:1, preferably 1.1 to 1.5:1, wherein the molar ratio of the alcohol to the acid refers to the molar ratio of the number of -OH and -COOH functional groups.
[0036] The esterification reaction is preferably:
[0037] The temperature is raised to 130-240° C. under protective gas conditions for esterification reaction, and the esterification reaction time is 1-5 hours; wherein the protective gas is a gas that does not affect the reaction process and does not react with the raw materials, preferably an inert gas or nitrogen.
[0038] The polymerization reaction is preferably:
[0039] Pre-condense at 190-250°C and 3kPa-10kPa for 1-4h; then evacuate to below 500Pa at 200-250°C and perform final condensation for 0.5-10h.
[0040] In a preferred embodiment of the present invention,
[0041] The butene glycol-based aliphatic-aromatic copolyester elastomer of the present application is a polyester elastomer in a patent application (application number 202110281347.8, invention name “A butene glycol-based aliphatic-aromatic copolyester elastomer and preparation method”), which is cited in its entirety herein.
[0042] The structural formula of the butene glycol-based aliphatic-aromatic copolyester elastomer is:
[0043]
[0044] R m , R n is a branched or unbranched chain alkyl or alkoxy group, R m , R n can be the same or different; wherein m, n represent the number of carbon atoms, 2≤m≤14; preferably 2≤m≤6; 2≤n≤14; preferably 2≤n≤6; the number of alkoxy groups is preferably 0 to 3;
[0045] R x , R y is a branched or unbranched chain alkyl group, R x , R y Can be the same or different; wherein x, y represent the number of carbon atoms, 4≤x≤14, preferably one of 4, 6, 10, 12; 4≤y≤14, preferably one of 4, 6, 10, 12;
[0046] R z is an aromatic ring or a furan ring; the aromatic ring is one of a benzene ring, a biphenyl ring, and a naphthalene ring;
[0047] a, b, c, d, e, f, g, h, i, and j represent the degree of polymerization;
[0048] Among them, a, b, e, f are not 0 at the same time; c and j are not 0 at the same time; g is not 0; d can be 0;
[0049] The butene glycol-based aliphatic-aromatic copolyester elastomer is prepared by subjecting a diol, an organic acid, an antioxidant, and a polymerization inhibitor to an esterification reaction and a polymerization reaction under the action of a catalyst to obtain the butene glycol-based aliphatic-aromatic copolyester elastomer;
[0050] The diols are 1,4-butene diol and saturated aliphatic diols;
[0051] The saturated aliphatic diol is C2~C 14 A branched or unbranched diol, preferably at least one of ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 2,3-butanediol, 1,4-cyclohexanedimethanol, diethylene glycol, triethylene glycol, and tetraethylene glycol;
[0052] The organic acid is a dibasic acid and lactic acid, or a dibasic acid;
[0053] The dibasic acid is a saturated aliphatic dibasic acid and an aromatic dibasic acid;
[0054] The saturated aliphatic dibasic acid is C4~C 14 A branched or unbranched dibasic acid, preferably at least one of succinic acid, adipic acid, sebacic acid, and dodecanedioic acid;
[0055] The aromatic dibasic acid is at least one of terephthalic acid, phthalic acid, isophthalic acid, biphenyl dicarboxylic acid, naphthalene dicarboxylic acid and furan dicarboxylic acid;
[0056] The molar percentage of 1,4-butenediol to diol is 2% to 60%, preferably 5% to 30%;
[0057] The molar percentage of the aromatic dibasic acid in the dibasic acid is 3% to 50%, preferably 5% to 40%;
[0058] The molar ratio of -OH to -COOH functional groups in diols and organic acids is (1.1-2):1; preferably (1.1-1.7):1;
[0059] The amount of the catalyst used is 0.05% to 1.0% of the total mass of the diol and the organic acid; preferably 0.1% to 0.6%;
[0060] The amount of antioxidant used is 0.01% to 0.5% of the total mass of diol and organic acid; preferably 0.05% to 0.2%;
[0061] The amount of the polymerization inhibitor is 0.01% to 0.5% of the total mass of the diol and the organic acid; preferably 0.05% to 0.2%;
[0062] The catalyst is at least one of selenium dioxide, antimony trioxide, antimony glycol, p-toluenesulfonic acid, acetate, alkyl aluminum with 1 to 12 carbon atoms, organic tin compounds, and titanate; preferably at least one of tetrabutyl titanate and tetraisopropyl titanate; and / or,
[0063] The antioxidant is at least one of phosphoric acid and phosphorous acid compounds; preferably at least one of phosphoric acid, phosphorous acid, phosphate ester, phosphite ester, phenyl phosphate, and phenyl phosphite; and / or,
[0064] The polymerization inhibitor is at least one of phenolic polymerization inhibitors, etheric polymerization inhibitors, quinone polymerization inhibitors, and aromatic amine polymerization inhibitors; preferably at least one of hydroquinone, p-tert-butylcatechol, p-hydroxyanisole, benzoquinone, diphenylamine, and p-phenylenediamine;
[0065] Preferably, 30% to 40% of the total mass of the catalyst is added in the esterification reaction stage, and the remaining catalyst is added in the pre-condensation stage of the polymerization reaction;
[0066] The esterification reaction is carried out by heating the temperature to 130°C to 240°C under protective gas conditions, and the esterification reaction time is 2h to 6h;
[0067] The polymerization reaction is performed by pre-condensation at 190°C to 250°C and 3kPa to 10kPa for 1h to 4h; then, at 200°C to 250°C, vacuum is drawn to below 500Pa, and final condensation is performed for 0.5h to 10h.
[0068] In a preferred embodiment of the present invention,
[0069] The nano filler is at least one of white carbon black and carbon black; white carbon black and carbon black are both common brands of rubber compositions for tire treads, wherein white carbon black is preferably one of A200 and VN3, and carbon black is preferably one of N330 and N234;
[0070] The peroxide crosslinking agent is at least one of dicumyl peroxide, di-tert-butyl dicumyl peroxide, and 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane.
[0071] In a preferred embodiment of the present invention,
[0072] The other compounding aids are at least one of a rubber processing aid, a cross-linking aid, a silane coupling agent, and a colorant; other compounding aids can be used in combination according to the commonly used amount of rubber as long as they do not violate the purpose of the present invention;
[0073] At least one of the rubber processing aids stearic acid, palmitic acid, and oleic acid;
[0074] The auxiliary cross-linking agent is at least one of triallyl isocyanurate, trimethylolpropane trimethacrylate, and N,N'-m-phenylene bismaleimide;
[0075] The silane coupling agent is at least one of γ-methacryloxypropyltrimethoxysilane (KH570), γ-aminopropyltriethoxysilane (KH550), and bis-γ-triethoxysilylpropyl tetrasulfide (Si69);
[0076] The colorant is at least one of titanium dioxide, phthalocyanine green and permanent yellow.
[0077] The second object of the present invention is to provide a method for preparing a biodegradable butene glycol-based polyester elastomer tread rubber, comprising:
[0078] The biodegradable butene glycol-based polyester elastomer tread rubber is obtained by uniformly mixing raw materials including butene glycol-based polyester elastomer, nano filler, peroxide crosslinking agent and other auxiliary agents.
[0079] Preferred preparation steps:
[0080] (1) A butene glycol-based polyester elastomer, a nanofiller, a rubber processing aid, a silane coupling agent, and a colorant are mixed to obtain a masterbatch.
[0081] (2) Mixing a masterbatch with a peroxide crosslinking agent and an auxiliary crosslinking agent to obtain a final rubber mix.
[0082] During production, mixing can be carried out in general rubber mixing machinery, such as a double-roll open mill, a kneading machine, an internal mixer, etc.; and the final rubber mixture can also be produced into sheets using a double-roll open mill to facilitate subsequent testing, packaging, transportation and use.
[0083] The final rubber mix can be vulcanized on a general rubber vulcanization molding device. The vulcanization is carried out according to the usual rubber vulcanization process parameters, preferably the vulcanization process parameters: the vulcanization temperature is 150-180°C, preferably 160-170°C; the vulcanization time is according to the specific T90 of the crosslinking, usually 15-30 minutes; the vulcanization pressure is 15-25MPa.
[0084] Compared with the existing tread rubber materials, the present invention has the following advantages:
[0085] 1. The butene glycol-based polyester elastomer tread rubber material provided by the present invention has excellent mechanical properties and can meet the performance requirements of the tire in actual use;
[0086] 2. The butene glycol-based polyester elastomer tread rubber material provided by the present invention is biodegradable, filling the gap in the field of degradable tread rubber materials, and will not accumulate in the environment in large quantities after use to cause damage to the environment and human health.
[0087] 3. The ester bond of the butene glycol-based polyester elastomer itself has good compatibility with silica, which is conducive to the dispersion of silica in the elastomer matrix. Therefore, when using silica as a nanofiller, silane coupling agent is not required and silica can be well dispersed in the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0088] Figure 1 is a scanning electron microscope image of the surface of the tread rubber after vulcanization prepared in Example 1;
[0089] Figure 2 is a scanning electron microscope image of the surface of the tread rubber prepared in Example 1 after being vulcanized and buried in the soil for 3 months;
[0090] Figure 3 is a scanning electron microscope image of the surface of the tread rubber after vulcanization prepared in Example 2;
[0091] Figure 4 is a scanning electron microscope image of the surface of the tread rubber prepared in Example 2 after being vulcanized and buried in the soil for 3 months;
[0092] Figure 5 This is a scanning electron microscope image of the surface of the tread rubber after vulcanization prepared in Comparative Example 1;
[0093] Figure 6 This is a scanning electron microscope image of the surface of the tread rubber prepared in Comparative Example 1 after being vulcanized and buried in the soil for 3 months;
[0094] SEM scanning electron microscope: magnification 400 times. DETAILED DESCRIPTION
[0095] The present invention is described in detail below in conjunction with specific drawings and embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the content of the present invention still fall within the scope of protection of the present invention.
[0096] The butene glycol-based aliphatic polyester elastomer and the butene glycol-based aliphatic-aromatic copolyester elastomer used in the examples are homemade in the laboratory; the other raw materials used in the examples and comparative examples are conventional commercially available raw materials.
[0097] Rubber mechanical properties test: GB / T 528-1998;
[0098] Scanning electron microscope (SEM), model S-4800, produced by Hitachi, Japan;
[0099] Example 1
[0100] Preparation of butene glycol based polyester elastomer:
[0101] In a reaction kettle equipped with a mechanical stirrer, a heating device, a temperature measuring device, a nitrogen system and a vacuum system, 565 g (7.43 mol) of 1,3-propylene glycol, 669 g (7.43 mol) of 1,4-butanediol, 145 g (1.65 mol) of 1,4-butenediol, 1050 g (8.89 mol) of succinic acid, 770 g (3.81 mol) of sebacic acid, 0.32 g of phosphorous acid and 1.28 g of hydroquinone were added; then, the temperature was raised to 180° C. under a nitrogen atmosphere, and esterification was carried out at normal pressure for 2 hours; then, 0.1% of the total weight of the monomers was added with tetrabutyl titanate as a catalyst, and the temperature was raised to 220° C. and 3 kPa, and pre-condensation was carried out for 1 hour; finally, the temperature was evacuated to below 500 Pa at 220° C., and final condensation was carried out for 9 hours to obtain a butenediol-based polyester elastomer.
[0102] The structure of the prepared butene glycol-based polyester elastomer is as follows:
[0103]
[0104] Among them, m1=3, m2=4; n1=2, n2=8;
[0105] In addition, (a+c+e):(k+m+o)≈9.52:4.08.
[0106] The specific formula of the butene glycol-based polyester elastomer tread rubber is:
[0107]
[0108]
[0109] The preparation steps of the butene glycol-based polyester elastomer tread rubber are as follows: first, the butene glycol-based polyester elastomer raw rubber, white carbon black (A200), stearic acid, titanium dioxide and phthalocyanine green are mixed to obtain a masterbatch; then, the masterbatch is mixed with di-tert-butyl peroxide diisopropylbenzene to obtain a final mix.
[0110] The final rubber mix was compression-vulcanized on a conventional flat-plate vulcanizer at 160°C. After full vulcanization, it was taken out and cut into dumbbell-shaped specimens to test its mechanical properties.
[0111] Example 2
[0112] Preparation of butene glycol-based polyester elastomer: Same as Example 1.
[0113] The specific formula of the butene glycol-based polyester elastomer tread rubber is:
[0114]
[0115] The preparation steps of the butene glycol-based polyester elastomer tread rubber are as follows: first, the butene glycol-based polyester elastomer raw rubber, carbon black (N330) and palmitic acid are mixed to obtain a masterbatch; then, the masterbatch is mixed with di-tert-butyl peroxide diisopropylbenzene and triallyl isocyanurate to obtain a final rubber mix.
[0116] The final rubber mix was compression-vulcanized on a conventional flat-plate vulcanizer at 160°C. After full vulcanization, it was taken out and cut into dumbbell-shaped specimens to test its mechanical properties.
[0117] Example 3
[0118] Preparation of butene glycol based polyester elastomer:
[0119] Into a reaction kettle equipped with mechanical stirring, heating device, temperature measuring device, nitrogen system and vacuum system, 598g (6.63mol) 1,4-butanediol, 212g (2.41mol) 1,4-butenediol, 931g (10.33mol) lactic acid, 153g (1.29mol) succinic acid, 1306g (6.46mol) sebacic acid, 3.2g tri-(2,4-di-tert-butylphenyl) )-phosphite and 12.8g of p-hydroxyanisole; then, under a nitrogen atmosphere, the temperature was raised to 130°C, and esterification was carried out at normal pressure for 2h, and then the temperature was raised to 190°C, and esterification was continued at normal pressure for 2h; then, 0.05% of the total weight of the monomers was added with tetraisopropyl titanate as a catalyst, and the temperature was raised to 190°C and 10kPa, and pre-condensation was carried out for 4h; finally, vacuum was evacuated to below 500Pa at 210°C, and final condensation was carried out for 6h to obtain a butene glycol-based polyester elastomer.
[0120] The structure of the prepared butene glycol-based polyester elastomer is as follows:
[0121]
[0122] Among them, m1=4, m2=0 (equivalent to m1=m2=4); n1=2, n2=8;
[0123] In addition, (b+d+f):(a+e):(k+m)≈10.33:1.29:6.46.
[0124] The specific formula of the butene glycol-based polyester elastomer tread rubber is:
[0125]
[0126] The preparation steps of the butene glycol-based polyester elastomer tread rubber are as follows: first, the butene glycol-based polyester elastomer raw rubber, white carbon black (VN3), carbon black (N234), stearic acid and KH570 are mixed to obtain a masterbatch; then, the masterbatch is mixed with diisopropylbenzene peroxide to obtain a final rubber mix.
[0127] The final rubber mix was compression-vulcanized on a conventional flat-plate vulcanizer at 160°C. After full vulcanization, it was taken out and cut into dumbbell-shaped specimens to test its mechanical properties.
[0128] Example 4
[0129] Preparation of butene glycol based polyester elastomer:
[0130] 560 g (7.36 mol) of 1,3-propylene glycol, 663 g (7.36 mol) of 1,4-butanediol, 144 g (1.64 mol) of 1,4-butene glycol, 936 g (7.93 mol) of succinic acid, 687 g (3.40 mol) of sebacic acid, 209 g (1.26 mol) of terephthalic acid, 2.24 g of phosphorous acid and 2.56 g of hydroquinone were added to a reaction kettle equipped with a mechanical stirrer, a heating device, a temperature measuring device, a nitrogen system and a vacuum system; then, the temperature was raised to 190° C. in a nitrogen atmosphere, and esterification was performed at normal pressure for 3 hours; then, 0.2% of the total weight of the monomers was added with tetrabutyl titanate as a catalyst, and the temperature was raised to 200° C. and 8 kPa, and pre-condensation was performed for 3 hours; finally, the temperature was evacuated to below 500 Pa at 220° C., and final condensation was performed for 9 hours to obtain a butene glycol-based aliphatic-aromatic copolyester elastomer.
[0131] The structure of the prepared butene glycol-based aliphatic-aromatic copolyester elastomer is as follows:
[0132]
[0133] Among them, HO-R m -OH, HO-R n -OH corresponds to 1,3-propylene glycol and 1,4-butanediol; HOOC-R x -COOH, HOOC-R y -COOH corresponds to succinic acid and sebacic acid; HOOC-R z -COOH corresponds to terephthalic acid;
[0134] In addition, (a+e+h):(b+f+i):(c+g+j)≈7.93:3.4:1.26.
[0135] The specific formula of the butene glycol-based polyester elastomer tread rubber is:
[0136]
[0137]
[0138] The preparation steps of the butene glycol-based polyester elastomer tread rubber are as follows: first, the butene glycol-based polyester elastomer raw rubber, white carbon black (A200), stearic acid, and trimethylolpropane trimethacrylate are mixed to obtain a masterbatch; then, the masterbatch is mixed with 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane and trimethylolpropane trimethacrylate to obtain a final rubber mix.
[0139] The final rubber mix was compression-vulcanized on a conventional flat-plate vulcanizer at 160°C. After full vulcanization, it was taken out and cut into dumbbell-shaped specimens to test its mechanical properties.
[0140] Comparative Example 1
[0141] Comparative Example 1 of the present application is Comparative Example 1 in the patent (patent number is CN104725756B, the invention name is "A kind of itaconate / isoprene copolymer type bio-based elastomer tread rubber and preparation method"), which is a tread rubber developed by a tire factory based on traditional rubber;
[0142] The specific formula is:
[0143]
[0144] Put the solution polymerized styrene butadiene rubber and cis-1,2-butadiene rubber on an open mill and plasticize for 3 minutes, add zinc oxide, stearic acid, and antioxidant and mix for 2 minutes, add white carbon black and silane coupling agent and mix for 7 minutes. Put the first masterbatch into an internal mixer for heat treatment for 8 minutes, the mixing temperature is 140°C, the rotor rotates at 80r / min, take it out, and leave it for 2 hours to obtain the second masterbatch. Blend the second masterbatch with carbon black on an open mill for 2 minutes, add paraffin, accelerator, and sulfur and mix for 8 minutes to obtain the final rubber. Hot press vulcanize at 150°C on a flat vulcanizer, prepare various test samples, and test their mechanical properties.
[0145] Table 1 Performance test results of tread rubber samples of Examples 1 to 4 and Comparative Example 1:
[0146] Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Tensile strength(MPa) 20.6 17.9 18.4 20.7 20.6 100% tensile stress (MPa) 3.0 2.6 4.5 4.2 2.0 300% tensile stress (MPa) 11.4 15.9 17.8 17.3 11.3 Elongation at break (%) 450 335 307 341 436 Tear strength (kN / m) 46.3 32.6 39.0 45.7 37.0 Shore A hardness 79 66 69 80 62 Degradation phenomenon Degradable Degradable Degradable Degradable Non-degradable
[0147] As shown in Table 1, the mechanical properties of the tread rubbers prepared in Examples 1 to 4 after vulcanization are comparable to those of the tread rubbers prepared in Comparative Example 1 of the prior art after vulcanization, showing excellent mechanical properties and meeting the mechanical property requirements of the tire in actual use.
[0148] like Figure 1 , Figure 3 , Figure 5 As shown in Figure 2, there were no holes on the surfaces of the three samples at the beginning. After being buried in the soil for 3 months, Figure 6 As shown in FIG. 1 , there are still no holes on the surface of the tread material of Comparative Example 1, which indicates that the tread rubber material developed based on traditional rubber materials is difficult to degrade. Figure 2 , Figure 4 As shown, after 3 months, holes appeared on the surface of the tread materials in both Example 1 and Example 2 due to microbial destruction, which indicates that the tread rubber material developed based on polyester elastomer is degradable. In addition, the degradation degree of the tread material in Example 1 is higher than that in Example 2, because the nanofiller in Example 1 is white carbon black, which can improve the hydrophilicity of the polyester elastomer tread rubber material compared to carbon black, making it more easily degraded and destroyed by microorganisms.
[0149] The butene glycol-based polyester elastomer tread rubber material prepared in Examples 1 to 4 is biodegradable and is a new type of degradable tread rubber material. It is more environmentally friendly to use and has broad application prospects.
Claims
1. A biodegradable butene glycol-based polyester elastomer tread rubber, characterized in that: The tread rubber is made of components including a butene glycol-based polyester elastomer, a nano filler, a peroxide cross-linking agent, and other compounding aids; Taking the butene glycol-based polyester elastomer as 100 parts by weight, the components are calculated by weight: The butene glycol-based polyester elastomer is a butene glycol-based aliphatic-aromatic copolyester elastomer; The structural formula of the butene glycol-based aliphatic-aromatic copolyester elastomer is: R m , R n is a branched or unbranched chain alkyl or alkoxy group, R m , R n can be the same or different; wherein m, n represent the number of carbon atoms, 2≤m≤14; 2≤n≤14; R x , R y is a branched or unbranched chain alkyl group, R x , R y Can be the same or different; wherein x, y represent the number of carbon atoms, 4≤x≤14; 4≤y≤14; R z is an aromatic ring or a furan ring; the aromatic ring is one of a benzene ring, a biphenyl ring, and a naphthalene ring; a, b, c, d, e, f, g, h, i, and j represent the degree of polymerization; Among them, a, b, e, f are not 0 at the same time; c and j are not 0 at the same time; g is not 0; d can be 0; The nano filler is at least one of white carbon black and carbon black; The other auxiliary agents are at least one of a cross-linking agent, a silane coupling agent, a colorant, stearic acid, palmitic acid, and oleic acid.
2. The butene glycol-based polyester elastomer tread rubber according to claim 1, characterized in that:
3. The butene glycol-based polyester elastomer tread rubber according to claim 1, characterized in that: In the structural formula of the butene glycol-based aliphatic-aromatic copolyester elastomer, 2≤m≤6; 2≤n≤6; the number of alkoxy groups is 0 to 3; x is one of 4, 6, 10, and 12; y is one of 4, 6, 10, and 12; The butene glycol-based aliphatic-aromatic copolyester elastomer is prepared by subjecting a diol, an organic acid, an antioxidant, and a polymerization inhibitor to an esterification reaction and a polymerization reaction under the action of a catalyst to obtain the butene glycol-based aliphatic-aromatic copolyester elastomer; The diols are 1,4-butene diol and saturated aliphatic diols; The saturated aliphatic diol is C2~C 14 Branched or unbranched diols; The organic acid is a dibasic acid and lactic acid, or a dibasic acid; The dibasic acid is a saturated aliphatic dibasic acid and an aromatic dibasic acid; The saturated aliphatic dibasic acid is C4~C 14 Branched or unbranched dibasic acids; The aromatic dibasic acid is at least one of terephthalic acid, phthalic acid, isophthalic acid, biphenyl dicarboxylic acid, naphthalene dicarboxylic acid and furan dicarboxylic acid; The molar percentage of 1,4-butenediol in diol is 2% to 60%; The molar percentage of the aromatic dibasic acid in the dibasic acid is 3% to 50%; The molar ratio of -OH to -COOH functional groups in diols and organic acids is (1.1-2):1; The amount of the catalyst used is 0.05% to 1.0% of the total mass of the diol and the organic acid; The dosage of the antioxidant is 0.01% to 0.5% of the total mass of the diol and the organic acid; The dosage of the polymerization inhibitor is 0.01% to 0.5% of the total mass of the diol and the organic acid; The catalyst is at least one of selenium dioxide, antimony trioxide, antimony glycol, p-toluenesulfonic acid, acetate, alkyl aluminum with 1 to 12 carbon atoms, organic tin compounds, and titanate; and / or, The antioxidant is at least one of phosphoric acid and phosphorous acid compounds; and / or, The polymerization inhibitor is at least one of a phenol polymerization inhibitor, an ether polymerization inhibitor, a quinone polymerization inhibitor, and an aromatic amine polymerization inhibitor; The esterification reaction is carried out by heating the temperature to 130°C to 240°C under protective gas conditions, and the esterification reaction time is 2h to 6h; The polymerization reaction is performed by pre-condensation at 190°C to 250°C and 3kPa to 10kPa for 1h to 4h; then, at 200°C to 250°C, vacuum is drawn to below 500Pa, and final condensation is performed for 0.5h to 10h.
4. The butene glycol-based polyester elastomer tread rubber according to claim 3, characterized in that: The saturated aliphatic diol is at least one of ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 2,3-butanediol, diethylene glycol, triethylene glycol, and tetraethylene glycol; and / or, The saturated aliphatic dibasic acid is at least one of succinic acid, adipic acid, sebacic acid and dodecanedioic acid; and / or, The molar percentage of 1,4-butenediol in diol is 5% to 30%; and / or, The molar percentage of the aromatic dibasic acid in the dibasic acid is 5% to 40%; and / or, The molar ratio of -OH to -COOH functional groups in the diol and the organic acid is (1.1 to 1.7):1; and / or, The amount of the catalyst used is 0.1% to 0.6% of the total mass of the diol and the organic acid; and / or, The amount of the antioxidant is 0.05% to 0.2% of the total mass of the diol and the organic acid; and / or, The amount of the polymerization inhibitor is 0.05% to 0.2% of the total mass of the diol and the organic acid; and / or, The catalyst is at least one of tetrabutyl titanate and tetraisopropyl titanate; and / or, The antioxidant is at least one of phosphoric acid, phosphorous acid, phosphate ester, phosphite ester, phenyl phosphate, and phenyl phosphite; and / or, The polymerization inhibitor is at least one of hydroquinone, p-tert-butylcatechol, p-hydroxyanisole, benzoquinone, diphenylamine and p-phenylenediamine; and / or, 30% to 40% of the total mass of the catalyst is added in the esterification reaction stage, and the remaining catalyst is added in the pre-condensation stage of the polymerization reaction.
5. The butene glycol-based polyester elastomer tread rubber according to claim 1, characterized in that: The peroxide crosslinking agent is at least one of dicumyl peroxide, di-tert-butyl dicumyl peroxide, and 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane.
6. The butene glycol-based polyester elastomer tread rubber according to claim 1, characterized in that: The auxiliary cross-linking agent is at least one of triallyl isocyanurate, trimethylolpropane trimethacrylate, and N,N'-m-phenylene bismaleimide; and / or, The silane coupling agent is at least one of γ-methacryloxypropyltrimethoxysilane and bis-γ-triethoxysilylpropyl tetrasulfide; and / or, The colorant is at least one of titanium dioxide, phthalocyanine green and permanent yellow.
7. A method for preparing a biodegradable butene glycol-based polyester elastomer tread rubber as claimed in any one of claims 1 to 6, characterized in that The method comprises: The biodegradable butene glycol-based polyester elastomer tread rubber is obtained by uniformly mixing raw materials including butene glycol-based polyester elastomer, nano filler, peroxide crosslinking agent and other auxiliary agents.
Citation Information
Patent Citations
Polyester type biological engineering rubber and preparation method thereof
CN101450985A
A bio-based elastomer tread compound of itaconic acid ester / isoprene copolymer and its preparation method
CN104725756B
Millable polyurethane tread-rubber carcass composite tire and manufacturing method thereof
CN106189198A
Aromatic-aliphatic polyester elastomer composite material and preparation method thereof
CN112708251A
Butenediol-based polyester elastomer and preparation method thereof
CN113136027A